Pengaruh Promosi Di Instagram Terhadap Keputusan Pembelian Konsumen Sepatu Di Masa Pandemi Covid 19 - Anis Farras Sina; Sigit Pramono Hadi (Lembaga Pengembangan Kinerja Dosen, 2023)
The purpose of this study was to determine whether there is a promotion effect on consumer decisions to buy shoe products at Rise and Risk online stores during the Covid 19 pandemic. The background of this research is considering that this pandemic is quite detrimental to business people and promotion through social media is the main thing to determine its effect on purchasing decisions. In this study, researchers used quantitative methods, namely research methods conducted by selecting samples through the purposive sampling technique. Data collection techniques in this study also went through a process, namely the distribution of questionnaires to respondents who were the subjects of this study. Respondents in this study were Instagram followers of the online store Rise and Risk, a sample of 100 respondents was taken. The data processing used in this research is using SPSS. The results obtained indicate that promotion has an influence on consumer purchasing decisions to buy shoe products at the Rise and Risk online store. The results of this study are to contribute in the field of communication, especially business communication.